التقييم الاقتصادي لإنتاج الكيوي في الساحل السوري - درويش, نضال (Latakia University Journal -Biological Sciences Series, 2018)
تعدّ زراعة الكيوي من الزراعات البديلة المهمة اقتصادياً، والتي أدخلت حديثاً إلى سورية، وذلك في عام 1986، إذْ بدأت زراعته في الغاب وحارم وحلب والشريط الساحلي وخاصة على ارتفاع ( 200- 300 م ) عن سطح البحر ولقد أثبت تأقلمه مع مناخ القطر العربي السوري. انطلاقاً من الأهمية الاقتصادية الكبيرة لزراعة الكيوي، فقد سعى هذا البحث إلى تحقيق الأهداف التالية: أ – تحليل التكاليف الإنتاجية لإنتاج الكيوي. ب – التقويم الاقتصادي لكفاءة زراعة الكيوي في الساحل السوري. نتيجة الدراسة تبين أن أهم النتائج التي توصل إليها البحث هي: 1) صافي الربح السنوي المحقق في الدونم الواحد يعادل (127.545 ) ألف ليرة سورية. 2) معامل الربحية بالقياس إلى رأس المال المستثمر يعادل (37.9 % ) ويعدّ هذا المؤشر جيداً. 3) معامل الربحية بالقياس إلى تكاليف الإنتاج بلغ ( 159.51 % ) وهذا المؤشر ممتاز. 4) مؤشر فترة استرداد رأس المال يعادل ( 2.63 ) سنة ويعدّ هذا المؤشر جيداً. Kiwi plantation is considered one of the economically important alternative cultivations, recently introduced to Syria namely in the year 1986. Its cultivation started in Alghab, Harem, Aleppo and the coastal strip, particularly at an altitude of 200 - 300 ms from sea level. It proved its orientation with the Syrian climate. Depending on the big economical importance of KIWI plantation, this research has aimed to meet the following targets: A) Analysis of production costs of KIWI production. B) Economical evaluation of KIWI production feasibility on the Syrian coast. The most important results of the study of the research are: 1) the annual net profit achieved per one dunum equals to ( 127,545 ) one thousand Syrian Pounds; 2) profitability coefficient in relation to the invested capital equals 37.9 %, and this is considered a good indication; 3) profitability coefficient in relation to production costs has amounted to 159.51 %, and this is considered an excellent indication; 4) indication of the capital refunding period equals 2.63 years, and this is considered a good indication.